2018
DOI: 10.3390/app8101993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Dermal Papilla Cells in Alginate Spheres

Abstract: Maintenance of trichogenecity of dermal papilla cells (DPCs) have been a problem during cell therapy for androgenic alopecia, as they lose their regenerative potential in in vitro culture. Various spheroid culture techniques are used to increase and maintain trichogenecity of these cells. However, there are some critical drawbacks in these methods. Applying a hydrocell plate for sphere formation or hanging drop methods by hand would be difficult to control the size and cell density inside it. It would be diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Here, we demonstrated that loliolide increased the cell viability and size of HDP spheroids. According to previous reports, DP cell numbers are increased during the anagen phase and affect the size and morphology of hair by providing a physical niche to influence the number of progenitor cells [31,38]. Also, decreased hair growth by DP leads to the miniaturization of the hair follicle in alopecia [39].…”
Section: ]mentioning
confidence: 92%
“…Here, we demonstrated that loliolide increased the cell viability and size of HDP spheroids. According to previous reports, DP cell numbers are increased during the anagen phase and affect the size and morphology of hair by providing a physical niche to influence the number of progenitor cells [31,38]. Also, decreased hair growth by DP leads to the miniaturization of the hair follicle in alopecia [39].…”
Section: ]mentioning
confidence: 92%
“…The size of the dermal papilla in the human hair follicle is approximately 100–250 µm [ 18 ]. In this study, to form a dermal papilla spheroid with a similar diameter of approximately 250 µm, we observed the spheroids by monitoring the microscopic images and staining cryosections with DAPI.…”
Section: Resultsmentioning
confidence: 99%
“…A controlled three-dimensional spherical model of DPC is made by converging the matrix components in a polymeric droplet on a flat surface using the droplet surface tension and the interaction with the gravitational field to form a cellular sphere for scalable induced DP microstructure fabrication . Interestingly, the spheres tended to take on a teardrop shape if a more diluted alginate solution is used, and the smaller number of cells inside the sphere, the more round the cluster is . Proper HF augmentation facilitates its entry into the growth cycle.…”
Section: Homeostatic Construction Of Hf Organoids Via a Biomaterials ...mentioning
confidence: 99%
“…The electrostatic spinning technique commonly used for full-thickness wound skin repair has also been used to prepare sodium alginate DP spheroids. It proved to maintain their hairiness, but their proliferation has not been seen for the time being . Chen et al used biocompatible and biodegradable gelatin and sodium alginate wrapped around HFSCs to construct a mimetic ECM and loaded transforming growth factor (TGF)-β2 into the coating as a slow-release signaling molecule that induces the conversion of CD34 + stem cells into highly proliferative Lgr5 + stem cells, similar to the partial activation of HFSCs in HF regeneration.…”
Section: Homeostatic Construction Of Hf Organoids Via a Biomaterials ...mentioning
confidence: 99%